Pigsticks and Harold and the Tuptown thief - Milway, Alex 1978- (Somerville, Massachusetts Candlewick Press, 2015)
There's a thief on the loose in Tuptown, and the annual Butterfly Ball will be canceled unless someone is brought to justice. Luckily, Pigsticks has crime-fighting in his blood and a magnifying glass in his hand. Will Detective Pigsticks and his keen-eyed assistant, Harold, solve the crime in time to save the ball?
Elementary Grade
Keywords: Animals -- Juvenile fiction; Hamsters -- Juvenile fiction; Parties -- Juvenile fiction; Swine -- Juvenile fiction; Thieves -- Juvenile fiction; Animals; Hamsters; Parties; Swine; Thieves; Fiction; Juvenile works